Research in labour economics. Vol. 36 - Polachek, S. W.; Tatsiramos, Konstantinos (Research in labor economics., 2012)
This volume contains eight new and innovative research articles relevant to researchers and policy makers. Each chapter deals with an aspect of human welfare and is authored by an expert in the field. One deals with how technological change affects the distribution of earnings, two deal with how workers advance through corporate hierarchy, four deal with how incentives motivate workers, and the final chapter deals with how one immigrant group is far more successful than even the native population. Among the questions answered are: What accounts for the relative rise in skilled worker salaries? Which workers advance more quickly up the corporate ladder? Are workers hired from outside the company as successful as internally promoted workers? Does performance-based pay affect worker absenteeism? Do retirement incentives to workers really help the firm? Do unexpected decreases in retirement income decrease retiree life satisfaction? Do more stringent divorce laws increase cohabitation? What causes immigrants to really succeed in their new country?.